45. KNOWLEDGE AND PRACTICE OF HPV VACCINATION AMONG ADULTS AGED 18-45 AT IMMUNIZATION CLINIC NO. 2 OF HANOI MEDICAL UNIVERSITY IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: To determine knowledge, practice, and some related factors regarding HPV vaccination among adults at Immunization Clinic No.2 of Hanoi Medical University in 2024.Subjects and methods: A cross-sectional descriptive study was conducted on 299 participants aged 18-45 at the vaccination clinic, Branch 2 of Hanoi Medical University, in 2024. The study used a questionnaire developed based on the Ministry of Health’s HPV prevention guidelines and referenced previous studies by Le Van Hoi in 2020.Results: The proportion of individuals with adequate knowledge about HPV vaccination among those aged 18-45 was low (24.41%). Individuals with sufficient knowledge had a higher vaccination rate (79.65%) compared to those with insufficient knowledge (20.35%) (p = 0.049). The rate of recommending the vắc-xin to others among those with adequate knowledge was 91.78%, compared to 8.22% in the group with insufficient knowledge (p = 0.008). Educational level and marital status were significantly associated with HPV vaccination knowledge (p < 0.05). No significant association was found with age (p = 0.124), occupation (p = 0.072), or income (p = 0.238).Conclusion: Study results indicate that adults aged 18-45 do not have sufficient knowledge about HPV vaccination. Educational level and marital status are influencing factors in HPV vaccination knowledge. Individuals with adequate knowledge were more likely to complete the vaccination compared to those with insufficient knowledge.
Keywords: Knowledge; practice; HPV vaccine